An annotated checklist of macrozoobenthic species in German waters of the North and Baltic Seas - Michael L. Zettler (Helgoland Marine Research, 2018)
Abstract The present compilation is the first attempt to generate a comprehensive list of all macrozoobenthic species recorded at least once in the German regions of the North Sea and Baltic Sea including non-indigenous species and freshwater species which occurred in brackish waters (estuaries, bays, fjords etc.). Based on the data of several research institutes and consultancies, the macrozoobenthic species inventory comprises a total of 1.866 species belonging to 16 phyla including 193 threatened species. The most common groups were: malacostracan crustaceans (21%), Polychaeta (19%), and Gastropoda (12%). Even though the two major marine regions are separated by only 50 km of land, the composition of the respective communities was different. The two seas shared only 36.6% of the recorded species which should have profound and far-reaching consequences for conservation purposes. Considering all macroinvertebrates listed 96 species, or the equivalent of 5.2%, were introduced mainly during the last two centuries. Both seas are heavily affected by human activities and are sensitive to climate change displayed by effects on the faunal compositions. The present checklist is an important step to document these changes scientifically and may act as a base for political and management decisions.